MEMELIHARA RUST EN ORDE: KASUS AGAMA JAWA SUNDA PASUNDAN - Mohammad Iskandar (Jurnal Masyarakat dan Budaya, 2012)
Many polemics took place because of the difference in interpretation about deviate religion, especially within the religious or the new beliefs. In this study, I select one case of deviationism which more or less represent two different era, namely the Religion of Java Sundanese Pasundan (Agama Jawa Sunda Pasundan-AJSP). According to colonial documents, the AJSP actually had appeared in Cigugur-Kuningan, West Java since the beginning of the 20th century. But the impact of its presence, especially that caused unrest among the society, only rose since the decade of the 1920s. Later, the unrest turned into a tension between support groups AJSP against Muslim Ummah around it. Especially after the AJSP leader, Kiai Madrais openly said that in the year of Alip, all religions will be disappeared but the AJSP. The tension eventually turned into some collective actions that accompanied by some violence. The AJSP side attacked group of Muslims and destroyed their properties. On the other occasion, the AJSP was the party that was attacked by muslim community around it. Keyword: Agama Jawa Sunda Pasundan (AJSP), Syncretism, Conflict, Tolerance.